Vegetation of Dakshina Kannada and Udupi districts of Karnataka, India - Bhat, K. Gopalakrishna (Rheedea, 2002)
Abstract of the Dr. V.V. Sivarajan Medal Lecture delivered on 26th September 2002 during the Twelfth Annual Conference of the Indian Association for Angiosperm Taxonomy held at Goa University. Goa.